Role of oxidative stress in the physiology of sensitive and resistant Amaranthus palmeri populations treated with herbicides inhibiting acetolactate synthase - Eceiza, Mikel Vicente; Barco-Antoñanzas, María; Gil-Monreal, Miriam; Huybrechts, Michiel; Zabalza, Ana; Cuypers, Ann; Royuela, Mercedes (Frontiers in Plant Science, 2023)
The aim of the present study was to elucidate the role of oxidative stress in the mode of action of acetolactate synthase (ALS) inhibiting herbicides. Two populations of Amaranthus palmeri S. Watson from Spain (sensitive and resistant to nicosulfuron, due to mutated ALS) were grown hydroponically and treated with different rates of the ALS inhibitor nicosulfuron (one time and three times the field recommended rate). Seven days later, various oxidative stress markers were measured in the leaves: H2O2, MDA, ascorbate and glutathione contents, antioxidant enzyme activities and gene expression levels. Under control conditions, most of the analysed parameters were very similar between sensitive and resistant plants, meaning that resistance is not accompanied by a different basal oxidative metabolism. Nicosulfuron-treated sensitive plants died after a few weeks, while the resistant ones survived, independently of the dose. Seven days after herbicide application, the sensitive plants that had received the highest nicosulfuron rate showed an increase in H2O2 content, lipid peroxidation and antioxidant enzymatic activities, while resistant plants did not show these responses, meaning that oxidative stress is linked to ALS inhibition. A supralethal nicosulfuron rate was needed to induce a significant oxidative stress response in the sensitive population, providing evidence that the lethality elicited by ALS inhibitors is not entirely dependent on oxidative stress.